2012
DOI: 10.3945/ajcn.111.020131
|View full text |Cite
|
Sign up to set email alerts
|

Intact sensory function in anorexia nervosa

Abstract: There is no systematic sensory-perceptual deficit in AN patients, and specifically, not in gustatory function. The few differences shown might be due to fear of food-related stimuli or comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
87
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(95 citation statements)
references
References 65 publications
6
87
1
1
Order By: Relevance
“…Goldzak‐Kunik et al (2012) found no differences across different food and nonfood tastes, but the fact that this was the only study to use food tastes (e.g., chocolate) as opposed to isolating specific taste qualities (e.g., sour, sweet), makes it difficult to compare and assess findings. The other nine studies assessed sweet, bitter, salty, and sour taste qualities, with inconsistent results.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Goldzak‐Kunik et al (2012) found no differences across different food and nonfood tastes, but the fact that this was the only study to use food tastes (e.g., chocolate) as opposed to isolating specific taste qualities (e.g., sour, sweet), makes it difficult to compare and assess findings. The other nine studies assessed sweet, bitter, salty, and sour taste qualities, with inconsistent results.…”
Section: Resultsmentioning
confidence: 93%
“…Of the two studies examining sweet, bitter, salty, and sour tastes, Goldzak‐Kunik et al (2012) found no differences in perceived intensity across these taste qualities. Jirik‐Babb and Katz (1988) found no difference in perceived intensity of sweetness, though did find evidence for lower intensity ratings of bitter, salty, and sour tastes in those with AN compared to HC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations